2014
DOI: 10.1177/2051013613515621
|View full text |Cite
|
Sign up to set email alerts
|

Successes and challenges in varicella vaccine

Abstract: Varicella is a highly contagious disease caused by primary infection with varicella zoster virus (VZV). VZV infection, as well as varicella vaccination, induces VZV-specific antibody and T-cell-mediated immunity, essential for recovery. The immune responses developed contribute to protection following re-exposure to VZV. When cell-mediated immunity declines, as occurs with aging or immunosuppression, reactivation of VZV leads to herpes zoster (HZ). It has been almost 20 years since universal varicella vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
1
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 139 publications
(195 reference statements)
1
69
1
13
Order By: Relevance
“…3,[12][13][14] Although this decreased the morbidity and mortality due to varicella, outbreaks were frequently reported among the vaccinated population. [15][16][17] The controversial causes of breakthrough infections were the age at vaccination, vaccine type, primary vaccine failure (not mounting protective immunity), or secondary vaccine failure (waning of protective immunity).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[12][13][14] Although this decreased the morbidity and mortality due to varicella, outbreaks were frequently reported among the vaccinated population. [15][16][17] The controversial causes of breakthrough infections were the age at vaccination, vaccine type, primary vaccine failure (not mounting protective immunity), or secondary vaccine failure (waning of protective immunity).…”
Section: Discussionmentioning
confidence: 99%
“…Varicella usually affects children aged 2-8 y. [1][2][3] Based on the universal nomenclature for VZV, VZV is categorized into 5 clades (clades [1][2][3][4][5]. While clades 1, 3, and 5 are common in Europe, clade 2 is most widely distributed in Japan and East Asia.…”
Section: Introductionmentioning
confidence: 99%
“…58 A model-based evaluation on the impact of varicella immunization on HZ in Italy has shown that an increase of HZ incidence related to varicella extensive immunization should be not certain. 59 In conclusion, evidence of an increase of HZ in countries with a universal varicella vaccination program is not consistent; 60 many studies have shown evidence of increasing incidence trends in HZ in countries with or without a universal varicella vaccination program. 61,62,63 Besides, in some countries, HZ incidence started to increase years before the vaccine was introduced.…”
Section: Can Zoster Vaccine Be Co-administered To Other Vaccines?mentioning
confidence: 90%
“…Ao longo do tempo tem-se assistido a um aumento da incidência da varicela nas crianças 1 com cerca de 95% dos adultos imunes na faixa etária dos 20 -29 anos. 2 Geralmente apresenta uma evolução auto-limitada e benigna, contudo pode associar-se a complicações e a necessidade de internamento em cerca de 2-6% dos casos. [3][4][5] A complicação mais frequentemente descrita é a sobreinfeção bacteriana da pele e tecidos moles, cujos agentes mais envolvidos são o Staphylococcus aureus e o Streptococcus pyogenes.…”
Section: Introductionunclassified